Toward an understanding of language : Charles Carpenter Fries in perspective - Fries, Peter Howard; Fries, Nancy M. (Amsterdam ; Philadelphia : J. Benjamins, 1985)
Charles C. Fries (1887-1967) was a major figure in American linguistics and language education during the first half of the 20th century. Theoretical innovation and practical implementation were important threads that ran throughout his work. Fries believed that the attempt to deal with practical problems was a vital part of developing linguistic theory. He spent most of his effort exploring grammar as a tool for communicating meaning. Charles C. Fries was quite influential in the development of linguistics in the United States, and yet in some ways remained outside of the mainstream of the li.
TOWARD AN UNDERSTANDING OF LANGUAGE CHARLES CARPENTER FRIES IN PERSPECTIVE; Editorial page; Title page; Copyright page; Dedication; PREFACE; Table of contents; INTRODUCTION; PART ONE: ENGLISH EDUCATION; EDUCATION OF ENGLISH TEACHERS; REFERENCES; CHARLES CARPENTER FRIES AND THE TEACHING OF LITERATURE; REFERENCES; CHARLES FRIES AND READING; REFERENCES; AMERICAN ENGLISH GRAMMAR; REFERENCES; PART TWO: LINGUISTICS AND THE ENGLISH LANGUAGE; C.C. FRIES' VIEW OF LANGUAGE AND LINGUISTICS; FOOTNOTES; REFERENCES; C.C. FRIES' SIGNALS MODEL OF ENGLISH GRAMMAR; FOOTNOTES; REFERENCES.
"Bibliography of Charles C. Fries": pages 359-372
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Fries, Charles C. -- 1887-1967.; Fries, Charles Carpenter, -- 1887- -- Critique et interprétation.; Fries, Charles C. -- 1887-1967; Fries, Charles Carpenter; Linguistics; English language -- Study and teaching; Linguistics; Linguistique; Anglais (Langue) -- Étude et enseignement; linguistics; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Historical & Comparative; English language -- Study and teaching; Linguistics; Linguistik; Englischunterricht; Aufsatzsammlung; Bibliografie; Sprachverstehen; Taalwetenschap; Criticism, interpretation, etc